Revolusi Pendidikan di Indonesia: Inovasi Pembelajaran untuk Menyiapkan Generasi Masa Depan yang Cerdas - Habsy, Bakhrudin All; Rizki, Reza Aulia; Lestari, Shafika Ayudyah (TSAQOFAH, 2024)
Qualitative research is defined as a scientific approach that aims to understand a phenomenon in depth. As there are various problems faced in learning, this hinders educators and students from understanding the material presented so that teaching and learning activities every year cannot predict the results, many learning innovations are created by educators who eventually have to learn new teaching methods to improve the quality of learning. With various new learning methods, not all of them are effective at one time. It is necessary for students and educators to adapt to follow learning methods in order to create quality with new strategies. Many things need to be considered to create new learning innovations so that the developed method can be successful as well as a solution to problems in teaching and learning activities, so that the method can be used by many individuals. The problems experienced in the world of learning are learning innovations such as technology development, affective learning, flipped classrooms, inclusive education, Artificial Intelligence, and project-based learning.